Sommerschulen "Fachsprache deutsch" – ideen, erfahrungsberichte und modelle - Bilitska, Viktoriya; Lange, Anja; Iatsenko, Nadiia (Ліра – К, 2017)
In this article shared are the experiences that the authors gained at two summer schools on the subject of the “German technical jargon”. Provided is the explanation of what technical jargon actually is and what has to be considered when teaching jargon at educational institutions. For instance, special terminology in the field of technology does not only consist of specific terms, but also requires additional competences that should be developed at such summer schools. Presented are the reports from both of the summer schools, 2016 under the topic “Car manufacture” and 2017 under the theme “Airplane construction”. Partucularly considered are the methods and tasks which are described and should inspire the holding of further similar events at summer schools.
Keywords: summer school; jargon; technique; methods